A reliability model of energy-efficient parallel disk systems with data mirroring. (9th August 2010) - Shen, Fangyang; Salazar, Andres; Qin, Xiao; Sun, Min-Te
In the last decade, parallel disk systems have increasingly become popular for data-intensive applications running on high performance computing platforms. Conservation of energy in parallel disk systems has a strong impact on the cost of cooling equipment and backup power-generation. This is because a significant amount of energy is consumed by parallel disks in high performance computing centres. Although a wide range of energy conservation techniques have been developed for disk systems, most energy saving schemes have adverse impacts on the reliability of parallel disk systems. To address this deficiency, we must focus on reliability analysis for energy-efficient parallel disk systems. In this paper, we make use of a Markov process to develop a quantitative reliability model for energy-efficient parallel disk systems using data mirroring. With the new model in place, a reliability analysis tool is developed to efficiently evaluate reliability of fault-tolerant parallel disk systems with two power modes. More importantly, the reliability model makes it possible to provide good trade-offs between energy efficiency and reliability in energy-efficient and fault-tolerant parallel disk systems.